Thermo diffusion and chemical effects with simultaneous thermal and mass diffusion in MHD mixed convection flow with ohmic heating - Reddy, N Ananda; Varma, SVK; Raju, MC (Journal of Naval Architecture and Marine Engineering, 2010)
Thermo diffusion and chemical effects on heat transfer in MHD mixed convection flow and mass transfer past an infinite vertical plate with Ohmic heating and viscous dissipation have been studied. Approximate solutions have been derived for velocity, temperature, concentration profiles, skin friction, rate of heat transfer and rate of mass transfer using perturbation technique. The obtained results are discussed with the help of graphs to observe the effect of various parameters like Schmidt number (Sc), Prandtl number (Pr), Magnetic parameter (M),Soret number (So) and chemical parameter (K), taking two cases viz. Case I: when Gr > 0 (flow on cooled plate) and Case II: Gr < 0 (flow on heated plate). Thermal diffusion causes both the fluid velocity and temperature to fall due to the presence of the chemical effect. Velocity and temperature profiles are higher for mercury than electrolytic solution. Soret effect increased the concentration of the fluid while chemical effect decreased. Keywords: Chemical effect; thermo diffusion; magnetic field; heat-mass transfer. DOI: 10.3329/jname.v6i2.3761